KAJIAN POTENSI GAS RUMAH KACA DARI SEKTOR SAMPAH DI TEMPAT PEMROSESAN AKHIR SAMPAH (TPA) RANDEGAN, KOTA MOJOKERTO - Rini, Titien Setiyo; Kusuma, Maritha Nilam; Pratiknyo, Yuwono Budi; Purwaningrum, Sri Wulan (2477 - 6165, 2020)
The final disposal of waste generation is a major environmental challenge in urban areas, especially in developing countries. Waste generation in developing countries will continue to grow as seen from the economic growth and changes in the consumptive patterns of the people, where current lifestyles and activities produce quantity of waste quickly. Waste is not only produced from households, but also from public facilities, such as school, institution, health, offices, markets, hotels, restaurants, and industries which later contribute to the generation of waste in the landfill. Waste management activities in landfills can produce various kinds of greenhouse gas emissions. This study aimed to determine the potential for greenhouse gas emissions from the rate of waste generation in Randegan TPA, Mojokerto City according to the parameters of the waste composition. Based on the research results, it was known that emissions generated from household waste amounted to 1.35 Gg CH4 and 3.72 Gg CO2, while non-domestic waste is 0.264 Gg CH4 and 0.728 Gg CO2.